Researching what matters to improve chronic pain care in Canada: A priority-setting partnership process to support patient-oriented research. Issue 1 (1st January 2018) - Poulin, Patricia; Shergill, Yaadwinder; Romanow, Heather; Busse, Jason W.; Chambers, Christine T.; Cooper, Lynn; Forgeron, Paula A.; Olsen Harper, Anita; Hudspith, Maria; Iorio, Alfonso; Lalloo, Chitra; Ouellette, Carley; et al.
ABSTRACT: Background: Chronic pain affects more than 6 million Canadians. Patients need to be involved in setting research priorities to ensure a focus on areas important to those who will be most impacted by the results. Aims: The aim of this study was to leverage patient experiences to identify chronic pain research priorities in Canada. Method: The process was informed by the James Lind Alliance. After gathering an exhaustive list of questions using surveys, town hall meetings, interviews, and social media consultations, we used a computerized Delphi with four successive iterations to select the final list of research priorities. The final Delphi round was conducted by a panel of ten patients living with chronic pain and ten clinicians from different disciplines. Results: We received more than 5000 suggestions from 1500 people. The Delphi process led to the identification of 14 questions fitting under the following 4 themes: (1) improving knowledge and competencies in chronic pain; (2) improving patient-centered chronic pain care; (3) preventing chronic pain and reducing associated symptoms; and (4) improving access to and coordination of patient-centered chronic pain care. Challenges included the issue of chronic pain being ubiquitous to many diseases, leading to many initial suggestions focusing on these diseases. We also identified the need for further engagement efforts with marginalized groups in order to validate the priorities identified or identify different sets of priorities specific to these groups. Conclusion: The priorities identified can guide patient-oriented chronic pain research to ultimately improve the care offered to people living with chronic pain.